2021
DOI: 10.1007/s12663-021-01532-1
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2, Uncontrolled Diabetes and Corticosteroids—An Unholy Trinity in Invasive Fungal Infections of the Maxillofacial Region? A Retrospective, Multi-centric Analysis

Abstract: Objectives Collate and analyse data of maxillofacial/rhino-cerebro-orbital fungal infections reported during the era of the Covid-19 pandemic, with the aim of investigating the common contributing factors leading to such infections and of highlighting the significance of this surge seen in patients infected with SARS-CoV-2. Method This retrospective observational multi-centric study analysed patient data collected from clinicians belonging to different specialties in Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
303
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(320 citation statements)
references
References 24 publications
11
303
0
6
Order By: Relevance
“…Six of these patients died, 11 survived and 1 was lost to follow up. Researchers confirmed significantly higher incidence of fungal infections (p = 0.03) amongst diabetic patients and suspect strong association with immunosuppression related to corticosteroid administration 50 .…”
Section: Discussionmentioning
confidence: 89%
“…Six of these patients died, 11 survived and 1 was lost to follow up. Researchers confirmed significantly higher incidence of fungal infections (p = 0.03) amongst diabetic patients and suspect strong association with immunosuppression related to corticosteroid administration 50 .…”
Section: Discussionmentioning
confidence: 89%
“…Apart from the viral-induced hyperglycemia, systemic steroids and antiviral agents used in the management of COVID-19 can also be considered as contributing factors in the worsening of hyperglycemia. There is an increased incidence of mucormycosis infections in diabetic patients treated for COVID-19, who received corticosteroid administration during the course of treatment [ 9 ]. Corticosteroids and immunosuppressive agents are risk factors and prolonged high dose (> 3 weeks) of corticosteroids predisposes an individual to angioinvasive Mucormycosis infection [ 30 ].…”
Section: Corticosteroidsmentioning
confidence: 99%
“…17,22,39,43,44 A recent case series of 18 patients with COVID-19 in India found that 16 developed mucormycosis, six of them with a fatal outcome (>37%). 28 Another series of 10 patients in India identified 10 patients with CAM, suggesting that this condition is more common than expected. 29 Treating physicians should have a high suspicion for CAM in patients with uncontrolled diabetes mellitus and severe COVID-19 presenting with rhinoorbital or rhino-cerebral syndromes.…”
mentioning
confidence: 97%
“…The increasing number of recent case series of mucormycosis complicating COVID-19 patients in the United States, 10 16 Austria, 17 Brazil, 18 Mexico, 19 Italy, 20 France, 21 Iran, 22 – 24 and India, 25 34 raises concerns regarding the misuse of immunosuppressive drugs in patients with COVID-19. Mucormycosis is a neglected mycosis that should be considered in the context of patients with COVID-19, in the same way as COVID-19 associated pulmonary aspergillosis, and it is possibly underreported.…”
mentioning
confidence: 99%